Synthesis and Characterization of Some Amides Containing Isoxazoline Ring - Ali, Kh. F.; Hussein, Dh. F; Tomma, J. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This work involves synthesis of amides containing isoxazoline unit starting with chalcone; 4-[3-(3‾-nitrophenyl)-2-propene- 1-one]-aniline[I]. 4-Aminoacetophenone was reacted with 3-nitrobenzaldehyde in basic medium giving chalcone [I] by claisen-schemidt reaction. The chalcone [I] was reacted with hydroxylamine hydrochloride giving isoxazoline [II] in NaOH basic medium. The amides with structural formula [III]a-h were prepared by the reaction of amino compounds ; isoxazoline [II] with different acid chlorides in dry pyridine and using DMF as a solvent at 4 0 C. All the synthesized compounds have been characterized by melting points , FTIR and 1 HMNR (of compound [III]a) spectroscopy.